Role of paraspinal muscle degeneration in the occurrence and recurrence of osteoporotic vertebral fracture: A meta-analysis - Chen, Zhi; Shi, Tengbin; Li, Wenwen; Sun, Jun; Yao, Zhipeng; Liu, Wenge (Frontiers in Endocrinology, 2023)
Purpose: Recently, the effects of paraspinal muscle degeneration on osteoporotic vertebral fractures (OVFs) have attracted the attention of researchers; however, studies are limited, and their results vary. Hence, this study aimed to determine the role of paraspinal muscle degeneration in the occurrence and recurrence of OVF. Methods: Following the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guideline, the PubMed, Embase, Web of Science, Wanfang Data, China National Knowledge Infrastructure, and ClinicalTrials.gov databases were comprehensively searched for relevant studies. Studies comparing the cross-sectional area (CSA) or fatty infiltration (FI) of the paraspinal muscles (including the psoas (PS), erector spinae plus multifidus (ES+MF), quadratus lumborum) in patients with and without initial OVF, or with and without recurrent OVF were included and analyzed. Results: Eleven studies were included in the meta-analysis. Seven studies investigated the effects of paraspinal muscles on initial OVF, and the overall results revealed significantly lower CSAES+MF (SMD: -0.575, 95% CI: -0.866 to -0.285) and CSAPS (SMD: -0.750, 95% CI: -1.274 to -0.226), and higher FI (SMD: 0.768, 95% CI: 0.475 to 1.062) in the fracture group. Meanwhile, four studies evaluated the effects of the paraspinal muscles on recurrent OVF, and the pooled results demonstrated significantly higher FI (SMD:0.720, 95% CI: 0.258 to 1.182) in the refracture group, although no significant difference in CSAES+MF (SMD: -0.103, 95% CI: -0.395 to 0.189) was observed between the two groups. Conclusions: Paraspinal muscle degeneration plays a role in the occurrence and recurrence of OVF. Assessing the paraspinal muscles may be useful for identifying high-risk populations.